Improvement of salinity tolerance in rice during boro season by proline application - Jahan, F; Bhusan, D; Jahiruddin, M; Murata, Y; Hoque, MA (Progressive Agriculture, 2019)
Salinity causes cellular damage, limiting crop productivity. Accumulation of proline is one of the main adaptive mechanisms to salinity in plants. The main objective of this study was to mitigate the adverse effects of soil salinity in boro rice by exogenous application of proline. The field experiment was conducted at the farmer’s field of Botiaghata, Khulna with Boro rice. The soil was silty clay loam having pH 7.2, EC 6.6 dS/m, CEC 26 meq/100 g soil and organic matter content 0.84%. Two rice varieties (salt-sensitive; BRRI dhan29 and salt-tolerant; BINA dhan-8) were used as test crops. There were ten treatment combinations with different concentrations of proline applied at seedling and/or vegetative stages. Recommended doses of N, P, K, S and Zn fertilizers were applied to the all experimental plots. The experiments were laid out in a randomized complete block design with three replications. Soil salinity caused a significant reduction in growth and yield of both salt-sensitive and salt-tolerant rice. Salt-tolerant rice produced higher grain and straw yields than salt-sensitive rice. Application of proline significantly increased growth, and grain and straw yields of boro rice under saline condition. There were no considerable variations in growth and yield of rice due to the different doses of proline. Increased nutrient uptake and K+/Na+ ratio in boro rice were observed due to proline application. The present study suggests that exogenous proline improves salt tolerance in rice by increasing K+/Na+ ratio and nutrient uptake. Progressive Agriculture 29 (4): 295-303, 2018